PENGARUH BUDAYA ORGANISASI, PERILAKU TIDAK ETIS DAN KEADILAN PROSEDURAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PENGELOLAAN DANA DESA DI DESA GOHONG KECAMATAN KAHAYAN HILIR KABUPATEN PULANG PISAU - Lorensa Kristina; Mutmainah Mutmainah; Maureen Marsenn (Balance: Media Informasi Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of organizational culture, unethical behavior, procedural justice on the tendency of accounting fraud. This study uses a quantitative approach with primary data in the from of a questionnaire where the sample obtained is 87 people with a saturated sampling method. The data analysis technique in this study uses SPSS 25 data analysis. The results of hypothesis testing indicate that organizationnal culture, unethical behavior and procedural justice have a negative and significant effect on the tendency of accounting fraud. It is recommended for further researchers to develop samples and are expected to be able to test with other variablesoutside the study